The great alaska adventure eaudiobook - Corwin, Jeff (Junior Explorer, 2010)
Host of the popular television show Corwin's Quest, author Jeff Corwin offers this second installment of his Junior Explorer series, The Great Alaska Adventure. Here Corwin proves that fun can be found right around the corner, as young adventurers discover the wonderful, exciting terrain and wildlife of Alaska.